An Analysis of Language Styles Used on Aaron Beverly Speech “An Unbelievable Story” in Toastmaster Public Speaking World Champion 2019 - Anggi Satmaya Dhila; Syafrizal Sabarudin; Arasuli Arasuli (Journal of English Education and Teaching, 2022)
This research aims to find out types of using language style on speech by Aaron Beverly, titled “Unbelievable Story and the possible reason why the style use dominantly. The method used in this research was descriptive quantitative research. The data were analyzed with using Martin Joos Theory (1976) to find the types of the style. The data were 70 utterances from 1 speech script. The findings showed that there were 4 styles used in the speech, namely frozen style, formal style, casual style and intimate style. The language style of the speech tended to have casual style as the most dominant style. It was possible to the speaker making an interesting light speech with the dominant casual style. The speech might be presented in fun topic and chronology where it became informal situation which was more relaxed in using language. Finally, the researcher suggests to the student to be able implement the style in presentation class or in learning public speaking. Also, the next researcher who interest to conduct research in the same study to connecting research to the next new literary ideas such as in public speaking skills in business.